Plasmid profile study of Listeria isolates from foods of animal origin - KATRE, D D; ZADE, N N; SHINDE, S V; JAULKAR, A D; KHAN, W A; CHAUDHARI, S P (The Indian Journal of Animal Sciences, 2011)
Nine isolates of Listeria species from the foods of animal origin were processed for plasmid profile studies, using the techniques of alkaline lysis and agarose gel electrophoresis. Of the 9 isolates, 8 harboured 1 to 2 plasmid fragments of varying molecular weight. The molecular weight of plasmid fragments was between 16148.78 bp and 698.00 bp; for L. murrayi; for L. grayi it was between 14261.73 bp and 10070.78 bp. L. ivanovii and L. innocua revealed single plasmid of molecular weight 10584.01 bp and 9171.78 bp respectively. Our findings indicate that plasmid profile is a valuable epidemiological tool in differentiating the strains with different sources of origin.